Linguistically Modulated Perception and Cognition: The Label-Feedback Hypothesis - Lupyan, Gary (Frontiers in Psychology, 2012)
How does language impact cognition and perception? A growing number of studies show that language, and specifically the practice of labeling, can exert extremely rapid and pervasive effects on putatively non-verbal processes such as categorization, visual discrimination, and even simply detecting the presence of a stimulus. Progress on the empirical front, however, has not been accompanied by progress in understanding the mechanisms by which language affects these processes. One puzzle is how effects of language can be both deep, in the sense of affecting even basic visual processes, and yet vulnerable to manipulations such as verbal interference, which can sometimes nullify effects of language. In this paper, I review some of the evidence for effects of language on cognition and perception, showing that performance on tasks that have been presumed to be non-verbal is rapidly modulated by language. I argue that a clearer understanding of the relationship between language and cognition can be achieved by rejecting the distinction between verbal and non-verbal representations and by adopting a framework in which language modulates ongoing cognitive and perceptual processing in a flexible and task-dependent manner.